Can Janus kinase inhibitors be used to treat immune checkpoint inhibitor associated adverse events? - Jürgen Braun; Kirsten Karberg (Exploration of Musculoskeletal Diseases)
Immune checkpoint inhibitors (ICI) such as cytotoxic T-lymphocyte associated protein-4 (CTLA-4), programmed cell death-1 (PD-1), programmed death ligand-1 (PD-L1), and lymphocyte activation gene-3 (LAG-3) are increasingly used to treat cancer patients since they were shown to reduce tumor progression and increase survival of patients with different types of cancer. However, ICI may also affect self-tolerance and lead to immune-related adverse events (irAEs) which are not very frequent but can present in almost all organ systems including joints, tendons, and muscles. Indeed, arthritis and myositis are among the most frequent irAEs. Glucocorticoids, immunosuppressants, and biologics are used to treat affected patients. This commentary deals with the question of whether Janus kinase inhibitors could be an option in this clinical situation.